ANALISIS VARIABILITAS SPASIAL DAN TEMPORAL KONSENTRASI NITRAT DI LAUT HALMAHERA DAN LAUT BANDA MENGGUNAKAN METODE EMPIRICAL ORTHOGONAL FUNCTION (EOF) - Sihotang, Zetsaona; Mandang, Idris; Munir, Rahmawati (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2018)
The East Indonesian ocean water is highly complex waters where it has become the passage of water masses from Pacific Ocean to Indian Ocean. Halmahera Sea and Banda Sea has an important role as one of the global ocean current trajectory from Pacific Ocean to Indian Ocean. The movement of water masses that occuring in this region has affect the condition and its fertility. One of the nutrients that affect the process of the growth of the pythoplankton and other microorganism is nitrate and it has become one of the indicators of waters fertility. This research aims to find out the effect of temperature and salinity on the change of nitrate concentration using Empirical Orthogonal Function (EOF) method. This method is used to separate the spatial and temporal data linkage in order to obtain the dominant spatial and temporal patterns. The data that used for the analysis was obtained from the output of the HYCOM (Hybrid Coordinate Ocean Model) model + NCODA Global 1/12º Reanalysis. The result of the analysis showing that the nitrate concentration was highly sensitive on the change of temperature in the ocean specifically in the Banda Sea region. The nitrate concentration increased during the East Monsoon where the sea surface temperatures dropped to 25ºC. In the West Monsoon, the sea surface temperature is warmer than usual so that the Banda Sea has a low nitrate concentration. In other hand, salinity did not show a significant effect on changes of nitrate concentration in the region of the Banda Sea and Halmahera Sea.